FORMULASI DAN UJI STABILITAS SEDIAAN LOTION EKSTRAK AIR BUAH TOMAT (Solanum lycopersicum L.) - Karim, Nuraeni; Arisanty; Rante Pakadang, Sesilia (Jurnal Kefarmasian Akfarindo, 2022)
Tomato (Solanum lycopersicum L.) has antioxidant active compounds that can prevent skin cell damage due to the influence of free radicals. Lotion is a cosmetic product whose consistency is lower than cream, so that the use of lotion can be evenly distributed on the skin. This research purposed to formulated the preparation of tomatoes (Solanum lycopersicum L.) Water Extract lotion and to know the physical quality stability of the preparation of Tomato (Solanum lycopersicum L.) Water Extract lotion. Tomatoes was extracted by using freeze dryer and then it was formulated with concentration 1%, 3%, and 5% by using lotion base that consist of Stearic Acid, Dimethicone, Glycerin, Nipagin, Nipasol, Liquid Paraffin, Cetyl Alcohol, Triethanolamine, Vitamin E, Fragrance, Aquadest. The inspection of preparation quality consist of organoleptic test, homogeneity, pH, dispersion, viscosity, adhesion before and after accelerated stability storage. The results showed that the lotion preparation of Tomato Fruit Water Extract at all concentrations (1%, 3%, 5%) before and after storage was accelerated homogeneously, had a pH ranging from 7 – 7.81, viscosity 2622 – 5180 cp.s, dispersion power. 5.2 – 8 cm, and adhesion ranged from 10.09 – 44.71 seconds. Lotion preparations with concentrations of tomato fruit extract 1%, 3%, 5%, have met the requirements for topical preparations except for formula 1. Key words : Lotion, Tomato Fruit (Solanum lycopersicum L.) Water Extract, Stability Test, Formulation, Skin.